Diallel analysis of resistance to rice yellow mottle virus in African rice Oryza glabelrrima Steud - Paul, C.; Ng, N.Q.; Ladeinde, T.A. (1995)
The genetics of resistance to rice yellow mottle sobemovirus (RYMV) in O. glaberrima was studied in a 6 parent full diallel cross involving 4 resistant and 2 susceptible genotypes. F1 hybrids resulting from crosses between resistant and susceptible genotypes were susceptible. Susceptibility was close to complete dominance over resistance. Estimates of genetic parameters following Hayman's and Griffing's methods indicated that additive gene effects were sigificant and more important than non-additive ones in determining the expression of resistance to RYMV. The high heritability estimates in additive gene action suggested that the pedigree breeding method would be an effective approach to increasing the level of resistance to RYMV in O. glaberrima.